Koleksi Sel Telur dengan Teknik Laparoskopi untuk Produksi Embrio dan Transfer Embrio pada Domba - Mohamad Agus Setiadi; Iman Supriatna; Arief Boediono (Jurnal Ilmu Pertanian Indonesia, 2007)
An experiment was carried out to analyze the application of laparoscopic technique for oocyte collection, in vitro embryo production and embryo transfer in sheep. The first experiment was conducted to observe effect of gonadotropin stimulation on follicle development and laparoscopic technique for oocytes aspiration. In the second experiment, effect of culture system on the embryo development in vitro was assessed and in the third experiment, the application of laparoscopic for embryo transfer has been conducted. The result showed that single dose of gonadotrophin was sufficient to support follicle development significantly and it could help follicle visualization. It also showed that laparoscopic ovum-pick up could be conducted weekly without any restriction The second series experiment showed CR1aa culture system was better than TCM 199 (29.90°/o vs 8.00%) and the changing of media was required to ensure better metabolism process for embryos. The third experiment revealed that embryo transfer could be conducted with an aid from laparoscope. In conclusion, single dose PMSG stimulation is sufficient to support follicle development for /aparoscopic ovum-pick up, the culture media changing affects the successful rate of in vitro embryo production (8% vs 25.66%) and the laparoscopy technique can be used safely for embryo transfer on sheep.Keyword: laparoscopic, oocyte, embryo transfer, sheep